Modern methods of satellite geodesy - Kushnir, D. V. (ТДАТУ, 2020)
As a disadvantage of satellite systems, we can note the occurrence during their operation of an error caused by "multipath", which is caused by multiple re-reflections of the satellite signal from surrounding objects and surfaces before it enters the receiver antenna, as well as diffraction on small objects commensurate with the length waves in the path of the radio beam. In this case, the radio beam travels along a different path, which causes a change in its amplitude and phase.
Keywords: satellite geodesy; geodesy; satellite systems